Zinc-doped aluminum oxide-metal lithium composite negative electrode and preparation method thereof
By using zinc-doped aluminum oxide-metal lithium composite anode in the lithium battery negative electrode, and using gradient constant current and thermal zinc permeation treatment to form a three-dimensional porous skeleton, the problems of large volume fluctuations in the charge and discharge cycle of lithium batteries are solved, and high energy density and cycle stability are achieved.
Patent Information
- Application Number
- CN202411583642.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-18
AI Technical Summary
The existing lithium battery negative electrode materials fluctuate in large volume during the charge and discharge cycle and the growth of lithium dendrites, resulting in insufficient battery life and cycle stability.
Zinc-doped aluminum oxide-metal lithium composite negative electrode is used to form an oxide film through gradient constant current anodization, and thermal zinc permeation is used to form a three-dimensional porous framework, and lithium is injected through porous capillary action to form an ultra-thin composite lithium material.
It effectively inhibits the growth of lithium dendrites, reduces volume expansion, improves the energy density and cycle stability of the battery, and enhances safety performance.
Smart Images

Figure CN119650594A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials for lithium batteries, and in particular relates to a zinc-doped aluminum oxide-metal lithium composite negative electrode and a preparation method thereof. Background Art
[0002] The development of negative electrode materials for lithium batteries is crucial to improving battery performance, extending battery life and promoting the progress of the new energy industry. At present, although the cost of traditional graphite materials for negative electrodes of lithium batteries is low and the technology is mature, its theoretical specific capacity is limited (about 372mAh / g), which makes it difficult to meet the future demand for high-energy-density batteries. With the continuous improvement of battery life requirements in new energy vehicles, portable electronic devices and other fields, the development of negative electrode materials with higher energy density has become an inevitable trend. Lithium, a lightweight and highly active alkali metal element, is regarded as a key negative electrode material for the next generation of battery technology due to its extremely high theoretical specific capacity (3860mAh / g) and extremely low redox potential (-3.04V).
[0003] The traditional method is to use lithium metal powder or directly act on lithium foil to reduce the actual current density by increasing the surface area of the lithium negative electrode. This method has a lower production cost, but the cathode structure is not stable during the charge and discharge process. The "host-free" nature of the lithium metal negative electrode will cause the battery volume to expand infinitely, resulting in uneven lithium deposition on the electrode, exacerbating the growth of lithium dendrites.
[0004] Coating a layer of inorganic material on the surface of lithium metal as a protective layer is also a common method, especially the solution coating method is simple and has a good coating effect. However, since the inorganic coating layer on the surface of lithium metal is often thin and brittle, its integrity during the charge and discharge process is difficult to ensure and it is easy to break. In addition, the lithium ion conductivity of solid electrolytes at room temperature is generally low, so this method also has great limitations.
[0005] Three-dimensional skeleton composite metal lithium negative electrode has been a hot topic in recent years. It can effectively inhibit the growth of dendrites and greatly increase the number of battery cycles. However, due to the complex three-dimensional skeleton structure of different materials, metal lithium is often easily deposited on the surface of the three-dimensional skeleton, resulting in pore blockage. Metal lithium grows unevenly inside the three-dimensional skeleton, and the pore utilization rate inside the skeleton is low. The actual capacity retention rate is far lower than the theoretical value. In addition, this method is relatively complicated and difficult to apply on a large scale. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a zinc-doped aluminum oxide-metal lithium composite negative electrode and a preparation method thereof, aiming to solve at least one technical problem in the background technology.
[0007] The present invention is achieved in that:
[0008] The first aspect of the present invention is a method for preparing a zinc-doped aluminum oxide-metal lithium composite negative electrode, which comprises the following steps:
[0009] Using HEDP solution as electrolyte and the pretreated aluminum sheet as anode, the aluminum sheet is anodized by gradient constant current to form an oxide film on the surface of the aluminum sheet;
[0010] Removing the residual electrolyte on the surface of the oxidized aluminum sheet, placing it at the bottom of a zincizing tank and burying it in zincizing powder, and sequentially performing curing and heat treatment in a sealed environment to obtain a zinc-doped aluminum substrate with a zincizing surface;
[0011] A thin layer of resin is coated on the zinc-dipizing surface of the zinc-doped aluminum substrate for coating and protection, and the back of the zinc-dipizing surface of the zinc-doped aluminum substrate is polished to remove the oxide film to expose the aluminum base, and an aluminum wire is welded on it as a conductor;
[0012] Using NaCl solution as electrolyte, zinc-doped aluminum substrate after coating protection and polishing as anode, and lead plate as cathode, constant voltage electrolysis is performed to achieve membrane-based separation. When the aluminum substrate on the non-zinc-infiltrated surface is completely dissolved and the current returns to zero, it is taken out and the resin is removed. After cleaning, a three-dimensional porous skeleton of zinc-doped aluminum oxide is obtained.
[0013] The molten lithium is brought into contact with the edge of the zinc-doped alumina of the three-dimensional porous skeleton for 3 minutes to 5 minutes, and the lithium is injected into the three-dimensional porous skeleton by combining the porous capillary effect to obtain an ultra-thin composite lithium material with a three-dimensional skeleton structure, namely the zinc-doped alumina-metal lithium composite negative electrode.
[0014] Furthermore, the HEDP solution is used as the electrolyte and the pretreated aluminum sheet is used as the anode, and the aluminum sheet is anodized by a gradient constant current, so that an oxide film is formed on the surface of the aluminum sheet; the specific operation is as follows:
[0015] Prepare a 0.3 mol / L to 0.6 mol / L solution of etidronate (HEDP), heat and stir for at least 24 hours to obtain a HEDP solution as an electrolyte;
[0016] A 1mm to 2mm thick high-purity aluminum sheet is ultrasonically cleaned in ethanol, dried with cold air, etched with alkaline solution, cleaned with hot water, washed with water at room temperature, soaked in acid solution, and washed with water at room temperature to remove the self-passivation layer and oil stains on the surface of the aluminum sheet;
[0017] Constructing an electrode structure of cathode-anode-cathode in an electrolytic cell, using a treated aluminum sheet as an anode and a lead plate, titanium plate, steel plate or nickel plate as a cathode, loading the HEDP solution into the electrolytic cell, starting a circulating cooler, using ethanol as a cooling medium, and setting the electrolyte temperature in the electrolytic cell to -10°C to 10°C;
[0018] First slowly increase the current density for 5 minutes to adjust to 0.3A / dm 2 Oxidation is carried out for 5min to 10min, and then the current density is increased slowly for 5min to 10min to increase to 0.5A / dm 2 ~1.5A / dm 2 The oxidation time is 25 minutes to 90 minutes. During the reaction, magnetic stirring is used to make the temperature field of the electrolyte in the electrolytic cell uniform, and an oxide film grows on the surface of the aluminum sheet.
[0019] Furthermore, the alkali solution of the alkali solution etching includes: 60g / L-100g / L NaOH and 5g / L-20g / L Na2S, the temperature of the alkali solution etching is 60°C, and the time is 30s-60s; the temperature of the hot water cleaning is 60°C.
[0020] Furthermore, in the anodic oxidation, the total surface area ratio of the anode to the cathode is 1:8-16; the wires connecting the cathode, the anode and the power supply are made of pure titanium wire or pure aluminum wire.
[0021] Furthermore, according to weight ratio, the sherardizing powder comprises:
[0022] Zinc powder 70%~90%;
[0023] Zinc chloride 9% to 30%;
[0024] Ammonium chloride 1%~4%.
[0025] Furthermore, the curing is specifically carried out at a temperature of 60°C to 90°C for 8h to 16h; and the heat treatment is specifically carried out at a temperature of 380°C to 450°C for 18h to 36h.
[0026] Furthermore, the voltage of the constant voltage electrolysis is 12V to 20V.
[0027] The second aspect of the present invention provides a zinc-doped aluminum oxide-metal lithium composite negative electrode prepared by the above preparation method.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention integrates the zinc-doped alumina membrane as a three-dimensional porous skeleton into the battery negative electrode design to form a zinc-doped alumina-metal lithium composite negative electrode, which overcomes the significant volume fluctuation and lithium dendrite growth problems of the metal lithium negative electrode in the existing lithium battery during the charge and discharge cycle.
[0030] 2. The three-dimensional porous skeleton of the composite negative electrode of the present invention exhibits regular and parallel pore distribution characteristics, and its inner and outer pore diameters are uniform and controllable in size, forming a highly ordered pore structure, which realizes efficient space utilization during lithium deposition, thereby improving the energy density of the battery.
[0031] 3. The hot zinc-dip treatment during the preparation of the composite negative electrode of the present invention forms a pure Zn layer with extremely good conductivity on the surface of the aluminum-based material, and is controlled by the concentration gradient and diffusion dynamics. The Zn content in the three-dimensional porous skeleton shows a gradually decreasing trend from the bottom (zinc-dipped surface) to the outside (the back of the zinc-dipped surface). The structural characteristics of poor surface conductivity and excellent bottom induce metallic lithium to preferentially deposit at the bottom of the skeleton, realizing an orderly growth pattern of lithium from bottom to top in the skeleton, effectively inhibiting the deposition of metallic lithium on the outer surface of the skeleton and the formation of dendrites, thereby greatly enhancing the cycle stability and safety performance of the metallic lithium negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a surface morphology of the non-zinc-diffused surface of the zinc-doped aluminum oxide film of the three-dimensional porous skeleton prepared in Example 1 of the present invention;
[0033] Figure 2 This is a local tubular interface morphology of the non-zinc-infiltrated surface of zinc-doped alumina of the three-dimensional porous framework prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] A method for preparing a zinc-doped aluminum oxide-metal lithium composite negative electrode comprises the following steps:
[0036] (1) Using HEDP solution as electrolyte and the pretreated aluminum sheet as anode, anodizing the aluminum sheet by gradient constant current to form an oxide film on the surface of the aluminum sheet; specifically:
[0037] Prepare a 0.3 mol / L to 0.6 mol / L solution of ethodiphosphonic acid (HEDP), heat it to 60°C ± 5°C, and mechanically stir it at a speed of 200 r / min ± 50 r / min for at least 24 hours to obtain a HEDP solution as an electrolyte;
[0038] A 1mm-2mm thick high-purity aluminum sheet is ultrasonically cleaned in ethanol, dried with cold wind, and then etched with alkaline solution (60g / L-100g / L NaOH and 5g / L-20g / L Na2S, 60°C) for 30s-60s, washed with hot water (60°C deionized water), washed with water at room temperature, soaked with acid solution (40% HNO3, 25°C, 120s), and washed with water at room temperature to remove the self-passivation layer and oil stains on the surface of the aluminum sheet;
[0039] The treated aluminum sheet is used as the anode, and a stable metal plate (lead plate, titanium plate, steel plate, nickel plate, preferably lead plate) that does not react with the electrolyte is selected as the cathode. The HEDP solution is loaded into the electrolytic cell, and the circulating cooler is turned on. Ethanol is used as the cooling medium, and the electrolyte temperature in the electrolytic cell is -10°C to 10°C. In order to ensure the uniformity of the oxide film, a cathode is provided before and after the anode, that is, an electrode structure of cathode-anode-cathode is constructed in the electrolytic cell, and the total surface area ratio of the anode and the cathode is 1:8-16. The connecting wires of the cathode and the power supply are pure titanium wire or pure aluminum wire.
[0040] First slowly increase the current density for 5 minutes to 0.3A / dm 2 Oxidation was performed for 5 to 10 minutes, and then the current density was increased to 0.5 A / dm for 5 to 10 minutes. 2 ~1.5A / dm 2 The oxidation time is 25 to 90 minutes. During the reaction, magnetic stirring is used to make the temperature field of the electrolyte in the electrolytic cell uniform. After the oxidation is completed, an oxide film grows on the surface of the aluminum sheet.
[0041] In the anodizing process of this step, the high-purity aluminum sheet is used as the anode, and the anode generates aluminum oxide. The reaction equation is: 2Al(s)+3H2O(l)=Al2O3(s)+6H + +6e - ; Then aluminum oxide is formed on the surface of the high-purity aluminum sheet as an oxide film; the role of the gradient current is to first oxidize briefly under low current density conditions to play a buffering function, with the aim of making the tubular porous structure grow more uniformly and neatly, with the inner and outer tube diameters close in size, otherwise a disorderly distribution similar to that of a tree branch may grow.
[0042] (2) The anodized aluminum sheet is placed in acetone for ultrasonic cleaning for 10 minutes and then dried with cold air to remove the electrolyte remaining on the surface of the anodized aluminum sheet, and then placed in the bottom of a zincizing tank and buried in zincizing powder (70% to 90% zinc powder; 9% to 30% zinc chloride; 1% to 4% ammonium chloride). In a sealed environment, curing and heat treatment are performed in sequence. The curing is specifically performed at a temperature of 60°C to 90°C for 8h to 16h, and the heat treatment is specifically performed at a temperature of 380°C to 450°C for 18h to 36h. After cooling, the zincizing powder remaining on the surface is removed. Since the aluminum sheet is buried in the bottom of the tank, its bottom surface is directly in contact with the bottom of the tank and is almost not in contact with the zincizing powder. As a result, this surface will be zincized in a small amount or unevenly or not at all, while the other side (the back of the bottom surface of the aluminum sheet) is completely and evenly zincized to form a zincizing surface, and finally a zinc-doped aluminum substrate with a zincizing surface is obtained;
[0043] In a specific implementation, zinc powder and zinc chloride in the sherardizing powder are zinc sources. Zinc chloride can increase the reaction activity, thereby increasing the diffusion rate of the sherardizing process, promoting the thickening of the sherardizing layer, and improving the uniformity of the sherardizing layer; ammonium chloride can inhibit oxidation, which is beneficial to reducing the zinc oxide produced during sherardizing.
[0044] (3) coating the zinc-dipizing surface of the zinc-doped aluminum substrate with a thin layer of resin for coating and protection, polishing the back of the zinc-dipizing surface of the zinc-doped aluminum substrate to remove the oxide film to expose the aluminum base, and welding aluminum wire as a conductor;
[0045] (4) using NaCl solution as electrolyte, zinc-doped aluminum substrate after coating protection and polishing as anode, and lead plate as cathode, and performing 12V-20V constant voltage electrolysis to achieve membrane-based separation. When the aluminum substrate on the non-zinc-infiltrated surface is completely dissolved and the current returns to zero, it is taken out and immersed in anhydrous ethanol solution to remove the resin. After cleaning, a three-dimensional porous skeleton of zinc-doped aluminum oxide is obtained;
[0046] The mechanism of constant voltage electrolysis in this step is: the exposed aluminum base is oxidized by electricity into aluminum ions that enter the solution to form an aluminum oxide film. The aluminum oxide film itself is not conductive and will not be electrolyzed; in addition, due to the protection of the resin coating on the zinc-infiltrated surface, no electrolysis reaction occurs on this surface. The resin protection is mainly to prevent the electrolytic foam from contaminating the zinc-infiltrated surface and to ensure the integrity of the film; if the aluminum base is not removed by electrolysis in this step, an overly thick and dense aluminum base will be formed, and a porous skeleton cannot be formed.
[0047] (5) The molten lithium is brought into contact with the edge of the zinc-doped alumina of the three-dimensional porous framework for 3 to 5 minutes, and the lithium is injected into the three-dimensional porous framework by combining the porous capillary action to obtain an ultra-thin composite lithium material with a three-dimensional framework structure, namely the zinc-doped alumina-metal lithium composite negative electrode.
[0048] In order to deal with the significant volume fluctuation and lithium dendrite growth problems of the metal lithium negative electrode in the charge and discharge cycle of the lithium battery, the present invention innovatively integrates the zinc-doped aluminum oxide film as a three-dimensional porous skeleton into the battery negative electrode design. Compared with the traditional metal lithium foil negative electrode, this design promotes the deposition of metal lithium in the pores of the porous skeleton during the charging stage. This mechanism not only effectively curbs the excessive growth of lithium dendrites, but also significantly reduces the volume expansion effect caused by lithium deposition. During the discharge process, when the lithium in the composite metal lithium electrode dissolves, the porous skeleton structure can also maintain good structural stability to ensure the integrity of the electrode.
[0049] Although graphene porous skeletons have been widely used in related fields, their complex pore structure leads to a large randomness in the nucleation and deposition of metal lithium inside them, which is easy to form local aggregation and then cause pore blockage, which not only greatly reduces the actual energy density of the battery, but also easily leads to battery expansion. In contrast, the three-dimensional alumina skeleton proposed in this study shows regular pore distribution characteristics, and its internal and external pore diameters are uniform and controllable, forming a highly ordered pore structure. This structure achieves efficient space utilization during lithium deposition, thereby improving the energy density of the battery. Further zinc infiltration treatment of the three-dimensional alumina skeleton is controlled by concentration gradient and diffusion kinetics, so that the Zn content of the porous alumina skeleton from the bottom to the outside shows a trend of gradually decreasing. In addition, a layer of pure Zn with excellent conductivity is formed on the surface. This structural characteristic of poor surface conductivity and excellent bottom induces metal lithium to preferentially deposit at the bottom of the skeleton, realizing an orderly growth mode of lithium from bottom to top in the skeleton, effectively inhibiting the deposition and dendrite formation of metal lithium on the outer surface of the skeleton, thereby greatly enhancing the cycle stability and safety performance of the metal lithium negative electrode.
[0050] Example 1
[0051] This embodiment is a method for preparing a zinc-doped aluminum oxide-metal lithium composite negative electrode, and the specific steps are as follows:
[0052] S1. Preparation of oxide film on aluminum sheet
[0053] Weigh a certain amount of HEDP and prepare a HEDP solution with a concentration of 0.3 mol / L, heat it to 60°C and maintain it under mechanical stirring at a speed of 200 r / min for more than 24 hours until the solution is uniform and clear without obvious fluid;
[0054] A 1 mm thick high-purity aluminum sheet (purity ≥ 99.999%) was pre-treated by ultrasonic cleaning in ethanol for 30 min, drying with cold air, alkali etching with 60 g / L NaOH + 5 g / L Na2S solution at 60 ° C for about 60 s, cleaning with 60 ° C deionized water, and then cleaning with room temperature deionized water, soaking in 40% HNO3 for 120 s, and then cleaning with room temperature deionized water to achieve the effect of removing the surface self-passivation layer and oil stains;
[0055] The HERP solution after the above treatment is poured into a double-layer beaker, and an anodic oxidation reaction device is built in the beaker, wherein the high-purity aluminum sheet after pretreatment is used as the anode, the lead plate is used as the cathode, and the oxidation is carried out in the form of cathode-anode-cathode front and back double cathode arrangement. The total surface area ratio of the anode plate and the cathode plate is 1:8, and the connecting wires of the anode and cathode and the power supply are pure aluminum wires;
[0056] Before the anodic oxidation reaction, the circulating cooler was turned on, ethanol was used as the cooling medium, the temperature was -10°C, and constant current gradient anodic oxidation was performed. Specifically, the current density was increased to 0.3A / dm with a slow rise time of 5min. 2 Oxidation was performed for 5 minutes, and then the current density was increased to 0.5 A / dm for 5 minutes. 2 The oxidation time was 25 minutes, and magnetic stirring was used during the reaction to make the temperature field in the tank liquid uniform; the oxidized aluminum sheet was placed in acetone for ultrasonic cleaning for 10 minutes and then dried with cold air.
[0057] S2. Hot galvanizing treatment
[0058] The anodized aluminum sheet is placed at the bottom of the zincizing tank and buried in the zincizing powder (the proportion of zincizing powder is 71% zinc powder, 28% zinc chloride, and 1% ammonium chloride). After being sealed with high-temperature glue and bolts and nuts, it is first kept warm at 60°C for 8 hours to achieve solidification; then it is kept warm at 380°C for 18 hours for heat treatment; after the heat treatment is completed, the heating is turned off and the furnace is cooled to room temperature, the aluminum sheet is taken out, placed in acetone for ultrasonic cleaning for 30 minutes to remove the sticky zincizing powder, and then rinsed with deionized water and blown dry with cold air; finally, a zinc-doped aluminum substrate with a zincizing surface is obtained.
[0059] S3. Surface treatment of zinc-doped aluminum substrate
[0060] A thin layer of resin is coated on the zinc-dipped surface of the zinc-doped aluminum substrate for coating and protection; the back side of the zinc-dipped surface of the zinc-doped aluminum substrate is exposed, and the oxide film on this side is polished off with 600-grit sandpaper to expose the aluminum base inside, and aluminum wire is welded as a conductor.
[0061] S4. Preparation of three-dimensional porous framework of zinc-doped alumina
[0062] The zinc-doped aluminum substrate treated with S3 was placed in a 3.5wt.% NaCl solution and used as the anode, the lead plate as the cathode, and the aluminum substrate was electrolyzed under a constant voltage of 12V to achieve membrane-based separation. After the aluminum was completely dissolved, the current returned to zero, the anode material was taken out and immersed in anhydrous ethanol solution until the resin was completely dissolved, and then washed with deionized water and dried to obtain a three-dimensional porous skeleton of zinc-doped aluminum oxide. The surface morphology of the non-zinc-infiltrated surface is as follows Figure 1 As shown in Figure 2, the local tubular interface morphology is as follows: Figure 2 shown.
[0063] S5. Preparation of ultra-thin composite lithium materials with three-dimensional skeleton structure
[0064] The molten lithium is brought into contact with the edge of the zinc-doped alumina of the three-dimensional porous skeleton prepared in step S4 for 3 minutes. Since the nanoscale pores in the three-dimensional skeleton structure can provide extremely strong capillary force, the porous capillary action can realize the rapid and uniform injection of lithium into the three-dimensional skeleton, thereby obtaining a three-dimensional skeleton structure ultra-thin composite lithium material, which is the zinc-doped alumina-metal lithium composite negative electrode.
[0065] Example 2
[0066] This embodiment is a method for preparing a zinc-doped aluminum oxide-metal lithium composite negative electrode, and the specific steps are as follows:
[0067] S1. Preparation of oxide film on aluminum sheet
[0068] Weigh a certain amount of HEDP and prepare a HEDP solution with a concentration of 0.4 mol / L, heat it to 60°C and maintain it under mechanical stirring at a speed of 200 r / min for more than 24 hours until the solution is uniform and clear without obvious fluid;
[0069] A 1.5 mm thick high-purity aluminum sheet (purity ≥ 99.999%) was pre-treated by ultrasonic cleaning in ethanol for 30 min, drying with cold air, alkali etching with 80 g / L NaOH + 12 g / L Na2S solution at 60 ° C for about 50 s, cleaning with 60 ° C deionized water, and then cleaning with room temperature deionized water, soaking in 40% HNO3 for 120 s, and then cleaning with room temperature deionized water to achieve the effect of removing the surface self-passivation layer and oil stains;
[0070] The HERP solution after the above treatment is poured into a double-layer beaker, and an anodic oxidation reaction device is built in the beaker, wherein the high-purity aluminum sheet after pretreatment is used as the anode, the lead plate is used as the cathode, and the oxidation is carried out in the form of cathode-anode-cathode front and back double cathode arrangement. The total surface area ratio of the anode plate and the cathode plate is 1:12, and the anode and cathode and power supply connection wires are pure aluminum wires;
[0071] Before the anodic oxidation reaction, the circulating cooler was turned on, ethanol was used as the cooling medium, the temperature was 0°C, and constant current gradient anodic oxidation was performed. Specifically, the current density was increased to 0.3A / dm with a slow rise time of 5min. 2 Oxidation was performed for 8 minutes, and then the current density was increased to 1.5 A / dm for 10 minutes. 2 The oxidation time is 60 minutes, and magnetic stirring is used during the reaction to make the temperature field in the tank liquid uniform; the oxidized aluminum sheet is placed in acetone for ultrasonic cleaning for 10 minutes and then blown dry with cold air.
[0072] S2. Hot galvanizing treatment
[0073] The anodized aluminum sheet is placed at the bottom of the zincizing tank and buried in the zincizing powder (the proportion of zincizing powder is 88% zinc powder, 10% zinc chloride, and 2% ammonium chloride). After being sealed with high-temperature glue and bolts and nuts, it is first kept warm at 80°C for 10 hours to achieve solidification; then it is kept warm at 400°C for 30 hours for heat treatment; after the heat treatment is completed, the heating is turned off and the furnace is cooled to room temperature, the aluminum sheet is taken out, placed in acetone for ultrasonic cleaning for 30 minutes to remove the sticky zincizing powder, and then rinsed with deionized water and blown dry with cold air to finally obtain a zinc-doped aluminum substrate with a zincizing surface.
[0074] S3. Surface treatment of zinc-doped aluminum substrate
[0075] A thin layer of resin is coated on the zinc-dipped surface of the zinc-doped aluminum substrate for coating and protection; the back side of the zinc-dipped surface of the zinc-doped aluminum substrate is exposed, and the oxide film on this side is polished off with 600-grit sandpaper to expose the aluminum base inside, and aluminum wire is welded as a conductor.
[0076] S4. Preparation of three-dimensional porous framework of zinc-doped alumina
[0077] The zinc-doped aluminum substrate treated with S3 was placed in a 3.5wt.% NaCl solution and used as the anode, the lead plate as the cathode, and the aluminum substrate was electrolyzed under a constant voltage of 18V to achieve membrane-based separation. After the aluminum was completely dissolved, the current returned to zero, the anode material was taken out and immersed in anhydrous ethanol solution until the resin was completely dissolved, and then washed with deionized water and dried to obtain a three-dimensional porous skeleton of zinc-doped aluminum oxide.
[0078] S5. Preparation of ultra-thin composite lithium materials with three-dimensional skeleton structure
[0079] The molten lithium is brought into contact with the edge of the zinc-doped alumina of the three-dimensional porous skeleton prepared in step S4 for 4 minutes. Since the nanoscale pores in the three-dimensional skeleton structure can provide extremely strong capillary force, the porous capillary action can realize the rapid and uniform injection of lithium into the three-dimensional skeleton, thereby obtaining a three-dimensional skeleton structure ultra-thin composite lithium material, which is the zinc-doped alumina-metal lithium composite negative electrode.
[0080] Example 3
[0081] This embodiment is a method for preparing a zinc-doped aluminum oxide-metal lithium composite negative electrode, and the specific steps are as follows:
[0082] S1. Preparation of oxide film on aluminum sheet
[0083] Weigh a certain amount of HEDP and prepare a HEDP solution with a concentration of 0.6 mol / L, heat it to 60°C and maintain it under mechanical stirring at a speed of 200 r / min for more than 24 hours until the solution is uniform and clear without obvious fluid;
[0084] A 2 mm thick high-purity aluminum sheet (purity ≥ 99.999%) was pre-treated by ultrasonic cleaning in ethanol for 30 min, drying with cold air, alkali etching with 100 g / L NaOH + 20 g / L Na2S solution at 60°C for about 30 s, cleaning with 60°C deionized water, and then cleaning with room temperature deionized water, soaking in 40% HNO3 for 120 s, and then cleaning with room temperature deionized water to remove the surface self-passivation layer and oil stains;
[0085] The HERP solution after the above treatment is poured into a double-layer beaker, and an anodic oxidation reaction device is built in the beaker, in which the high-purity aluminum sheet after pretreatment is used as the anode, the lead plate is used as the cathode, and the oxidation is carried out in the form of cathode-anode-cathode front and back double cathode arrangement. The total surface area ratio of the anode plate and the cathode plate is 1:16, and the connecting wires of the cathode and the power supply are pure aluminum wires;
[0086] Before the anodic oxidation reaction, the circulating cooler was turned on, ethanol was used as the cooling medium, the temperature was 10 °C, and constant current gradient anodic oxidation was performed. Specifically, the current density was increased to 0.3 A / dm with a slow rise time of 5 min. 2 Oxidation was carried out for 10 minutes, and then the current density was increased to 1.5A / dm 2 The oxidation time is 90 minutes, and magnetic stirring is used during the reaction to make the temperature field in the tank liquid uniform; the oxidized aluminum sheet is placed in acetone for ultrasonic cleaning for 10 minutes and then blown dry with cold air.
[0087] S2. Hot galvanizing treatment
[0088] The anodized aluminum sheet is placed at the bottom of the zincizing tank and buried in the zincizing powder (the proportion of zincizing powder is 90% zinc powder, 9% zinc chloride, and 1% ammonium chloride). After being sealed with high-temperature glue and bolts and nuts, it is first kept warm at 90°C for 16 hours to achieve solidification; then it is kept warm at 4500°C for 36 hours for heat treatment; after the heat treatment is completed, the heating is turned off and the furnace is cooled to room temperature, the aluminum sheet is taken out, placed in acetone for ultrasonic cleaning for 30 minutes to remove the sticky zincizing powder, and then rinsed with deionized water and blown dry with cold air; finally, a zinc-doped aluminum substrate with a zincizing surface is obtained.
[0089] S3. Surface treatment of zinc-doped aluminum substrate
[0090] A thin layer of resin is coated on the zinc-dipped surface of the zinc-doped aluminum substrate for coating and protection; the back side of the zinc-dipped surface of the zinc-doped aluminum substrate is exposed, and the oxide film on this side is polished off with 600-grit sandpaper to expose the aluminum base inside, and aluminum wire is welded as a conductor.
[0091] S4. Preparation of three-dimensional porous framework of zinc-doped alumina
[0092] The zinc-doped aluminum substrate treated with S3 was placed in a 3.5wt.% NaCl solution and used as the anode, the lead plate as the cathode, and the aluminum substrate was electrolyzed under a constant voltage of 20V to achieve membrane-based separation. After the aluminum was completely dissolved, the current returned to zero, the anode material was taken out and immersed in anhydrous ethanol solution until the resin was completely dissolved, and then washed with deionized water and dried to obtain a three-dimensional porous skeleton of zinc-doped aluminum oxide.
[0093] S5. Preparation of ultra-thin composite lithium materials with three-dimensional skeleton structure
[0094] The molten lithium is brought into contact with the edge of the zinc-doped alumina of the three-dimensional porous skeleton prepared in step S4 for 5 minutes. Since the nanoscale pores in the three-dimensional skeleton structure can provide extremely strong capillary force, the porous capillary action can realize the rapid and uniform injection of lithium into the three-dimensional skeleton, thereby obtaining a three-dimensional skeleton structure ultra-thin composite lithium material, which is the zinc-doped alumina-metal lithium composite negative electrode.
[0095] Comparative Example 1
[0096] In this comparative example 1, an aluminum oxide-metal lithium composite negative electrode is prepared. The difference between this comparative example 1 and the example 1 is that no hot zincification treatment is performed. The specific steps of this comparative example 1 are as follows:
[0097] S1, the same as step S1 of embodiment 1;
[0098] S2, coating one side of the aluminum sheet with oxide film attached to the surface obtained in step S1 with a thin layer of resin for coating and protection, and using 600-mesh sandpaper to grind off the oxide film on the other side to expose the aluminum substrate inside, and welding aluminum wire as a conductor;
[0099] S3, the same as step S4 of embodiment 1;
[0100] S4 is the same as step S5 in Example 1, and the final material is an aluminum oxide-metal lithium composite negative electrode.
[0101] Comparative Example 2
[0102] In this comparative example 2, a zinc-doped aluminum oxide-metal lithium composite negative electrode is prepared. The difference between this comparative example 2 and the embodiment 1 is the anodizing reaction conditions of step S1. The specific steps of anodizing in this comparative example 2 are as follows:
[0103] Before the anodic oxidation reaction, the circulating cooler was turned on, ethanol was used as the cooling medium, the temperature was -10°C, and the anodic oxidation was carried out. Specifically, the current density was increased to 0.5A / dm for a slow rise time of 10min. 2 The oxidation time was 25 minutes, and magnetic stirring was used during the reaction to make the temperature field in the tank liquid uniform; the oxidized aluminum sheet was placed in acetone for ultrasonic cleaning for 10 minutes and then dried with cold air.
[0104] The other steps and reaction conditions of Comparative Example 2 are the same as those of Example 1, and the final material prepared is a zinc-doped aluminum oxide-metal lithium composite negative electrode.
[0105] The negative electrode materials prepared in Examples 1 to 3, Comparative Example 1 and Comparative Example 2 were subjected to electrochemical tests, specifically: the prepared negative electrode materials were punched to obtain composite electrode circular plates with a diameter of 15 mm; the circular plates were used as negative electrodes, LiFePO4 plates were used as positive electrodes, Celgard 2400 was used as diaphragms, 1M LiPF6 EC:DMC (1:1 Vol%) was used as electrolytes, and button cells were assembled in the order of positive electrode shell → positive electrode sheet → diaphragm → lithium sheet → gasket, shrapnel → negative electrode shell. The charge and discharge specific capacity was tested at a discharge rate of 1 C on a Land electrochemical instrument, and the initial discharge capacity and capacity retention rate obtained after 100, 300 and 1000 cycles are shown in Table 1.
[0106] Table 1
[0107]
[0108]
[0109] It can be seen from the data in Table 1 that after the negative electrode material prepared in the embodiment of the present invention is prepared into a battery, it still has a high capacity retention rate after cycling 100 times, 300 times, and 1000 times.
[0110] It can be seen from the data in Table 1 that both the discharge capacity and the capacity retention rate of Comparative Example 1 are low at each cycle number. The reason is that the conductivity of the porous skeleton without zinc infiltration is low, which will reduce the deposition rate, and compared with the porous skeleton with a zinc infiltration layer, lithium is no longer accumulated and deposited from the bottom to the top in an orderly manner, and the utilization rate of the space in the pores is low; and dead lithium is easily formed and removed, which greatly reduces the capacity retention rate.
[0111] It can be seen from the data in Table 1 that the discharge capacity of Comparative Example 2 is relatively low at each cycle number. This is because the pores of the oxide layer grown by anodization without multi-step voltage are arranged in a disorderly and uneven manner, the difference between the inner and outer pore sizes is large, and part of the space in the pores cannot be deposited and utilized during the charge and discharge process. The actual discharge capacity is much lower than the theoretical discharge capacity.
[0112] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a zinc-doped aluminum oxide-metal lithium composite negative electrode, characterized in that: The preparation method comprises the following steps: Using HEDP solution as electrolyte and the pretreated aluminum sheet as anode, the aluminum sheet is anodized by gradient constant current to form an oxide film on the surface of the aluminum sheet; Removing the residual electrolyte on the surface of the oxidized aluminum sheet, placing it at the bottom of a zincizing tank and burying it in zincizing powder, and sequentially performing curing and heat treatment in a sealed environment to obtain a zinc-doped aluminum substrate with a zincizing surface; A thin layer of resin is coated on the zinc-dipizing surface of the zinc-doped aluminum substrate for coating and protection, and the back of the zinc-dipizing surface of the zinc-doped aluminum substrate is polished to remove the oxide film to expose the aluminum base, and a pure aluminum wire is welded on it as a conductor; Using NaCl solution as electrolyte, zinc-doped aluminum substrate after coating protection and polishing as anode, and lead plate as cathode, constant voltage electrolysis is performed to achieve membrane-base separation, starting from the back of the zinc-diffused surface until the current returns to zero after the aluminum substrate is completely dissolved, then the oxide layer is taken out and the resin is removed, and after cleaning, a three-dimensional porous skeleton of zinc-doped aluminum oxide is obtained; The molten lithium is brought into contact with the edge of the zinc-doped alumina of the three-dimensional porous skeleton for 3 minutes to 5 minutes, and the lithium is injected into the three-dimensional porous skeleton by combining the porous capillary effect to obtain an ultra-thin composite lithium material with a three-dimensional skeleton structure, namely the zinc-doped alumina-metal lithium composite negative electrode.
2. The method for preparing a zinc-doped aluminum oxide-metal lithium composite negative electrode according to claim 1, characterized in that: The HEDP solution is used as the electrolyte and the pretreated aluminum sheet is used as the anode, and the aluminum sheet is anodized by a gradient constant current, so that an oxide film is formed on the surface of the aluminum sheet; the specific operation is as follows: Prepare a 0.3 mol / L to 0.6 mol / L solution of etidronate (HEDP), heat and stir for at least 24 hours to obtain a HEDP solution as an electrolyte; A 1mm to 2mm thick high-purity aluminum sheet is ultrasonically cleaned in ethanol, dried with cold air, etched with alkaline solution, cleaned with hot water, washed with water at room temperature, soaked in acid solution, and washed with water at room temperature to remove the self-passivation layer and oil stains on the surface of the aluminum sheet; Constructing an electrode structure of cathode-anode-cathode in an electrolytic cell, using a treated aluminum sheet as an anode and a lead plate, titanium plate, steel plate or nickel plate as a cathode, loading a HEDP solution into the electrolytic cell, starting a circulating cooler, using ethanol as a cooling medium, and controlling the electrolyte temperature in the electrolytic cell to -10°C to 10°C; First slowly increase the current density for 5 minutes to 0.3A / dm 2 Oxidation was performed for 5 to 10 minutes, and then the current density was increased to 0.5 A / dm for 5 to 10 minutes. 2 ~1.5A / dm 2 The oxidation time is 25 minutes to 90 minutes. During the reaction, magnetic stirring is used to make the temperature field of the electrolyte in the electrolytic cell uniform. After the oxidation is completed, an oxide film grows on the surface of the aluminum sheet.
3. The method for preparing a zinc-doped aluminum oxide-metal lithium composite negative electrode according to claim 2, characterized in that: The alkali solution for alkali etching includes: 60g / L-100g / L NaOH and 5g / L-20g / L Na2S. The temperature of the alkali solution etching is 60°C and the time is 30s-60s. The temperature of the hot water cleaning is 60°C.
4. The method for preparing a zinc-doped aluminum oxide-metal lithium composite negative electrode according to claim 2, characterized in that: The total surface area ratio of the anode to the cathode in the anodic oxidation is 1:8-16; the wires connecting the cathode, the anode and the power supply are made of pure titanium wire or pure aluminum wire.
5. The method for preparing a zinc-doped aluminum oxide-metal lithium composite negative electrode according to claim 1, characterized in that: According to weight ratio, the sherardizing powder comprises: Zinc powder 70%~90%; Zinc chloride 9% to 30%; Ammonium chloride 1%~4%.
6. The method for preparing a zinc-doped aluminum oxide-metal lithium composite negative electrode according to claim 1 or 5, characterized in that: The curing is specifically carried out at a temperature of 60° C. to 90° C. for 8 h to 16 h.
7. The method for preparing a zinc-doped aluminum oxide-metal lithium composite negative electrode according to claim 6, characterized in that: The heat treatment is specifically carried out at a temperature of 380° C. to 450° C. for 18 h to 36 h.
8. The method for preparing a zinc-doped aluminum oxide-metal lithium composite negative electrode according to claim 1, characterized in that: The voltage of the constant voltage electrolysis is 12V to 20V.
9. A zinc-doped aluminum oxide-metal lithium composite negative electrode prepared by the preparation method according to any one of claims 1 to 8.